PELAYANAN KESEHATAN PEDULI REMAJA MENURUT PERSPEKTIF REMAJA DI KOTA MAGELANG - Rohmayanti, Rohmayanti; Rahman, Irwan Taufiqur; Nisman, Wenny Artanty (IPAKESPRO, 2015)
Â Rohmayanti1, Irwan Taufiqur Rachman2, Wenny Artanty Nisman3Â ABSTRACTBackground:Teenagers have greater risk for health problems, especially sexuality and reproduction problems. Government has already developed Adolescent Friendly Health Services (AFHS). This program has already run in primary health care to overcome teenagerâs health problems. On the other hand, this program does not seem to accommodate some of teenagerâs expectation. Therefore, we need to conduct a research for knowing what kind of health services are suitable with teenagerâs perspective.Â Objective: This study was design to explore type of AFHS which were suitable in adolescentâs perspective. Method: In this qualitative study, phenomenology was used for the approach. This study was conducted from September-October 2014 in primary health care region of Magelang. The participants for this study were 10-19 years old teenagers and they had already received adolescent friendly health services. The participants had been chosen using purposive sampling. The data was collected using focus group discussion, observation and indepth interview. Colaizziâs analysis had been used for data analysis manually.Result and Discussion: Adolescentâs perspective about AFHS consist of three theme. The first theme was adolescent perspective on existence of AFHS which was still various. The second theme was the perception of adolescents on the AFHS given in adolescents.The result was that not all six AFHS programs were given. The Third theme was adolescents hope for the result was AFHS health workers should be able to provide an explanation of the problems experienced by adolescents, be friendly, and the need to involve youth, teachers, parents and the community in AFHS services. Health Services that are conducted in teenagers, should be confidential,the service time was able to adjust school hours, use short massage, email for communication and information.Conclusion: adolescentâs have various expectations of the AFHS services in the future. Health services in accordance with the expectations of adolescents can be developed as a modified form of health care that can be implemented in AFHS primary health care.Keywords: Adolescent Friendly Health Services (AFHS), Adolescent.ABSTRAKLatar Belakang: Remaja sangat rentan terhadap berbagai ancaman risiko kesehatan terutama seksual dan reproduksi. Pemerintah telah mengadakan program Pelayanan Kesehatan Peduli Remaja (PKPR) yang dilaksanakan di puskesmas untuk mengatasi masalah kesehatan remaja. Program PKPR yang sudah berjalan, belum mengakomodir kepentingan remaja, sehingga perlu diketahui bagaimana pelayanan kesehatan peduli remaja yang sesuai dengan perspektif remaja.Tujuan: Mengetahui pelayanan kesehatan peduli remaja (PKPR) menurut perspektif remaja.Metode:Penelitian kualitatif dengan pendekatan fenomenologi. Subjek penelitian adalah remaja usia 10-19 tahun yang telah mendapatkan pelayanan kesehatan peduli remaja, dipilih secara purposive sampling. Pengumpulan data dengan cara FGD, observasi dan wawancara. Analisa data dilakukan secara manual, menggunakan tahapan analisa data menurut Colaizzi (1978). Penelitian dilakukan pada bulan September-Oktober 2014, di puskesmas wilayah Kota Magelang.Â Hasil dan Pembahasan: Perspektif remaja tentang PKPR terdiri atas tiga tema. Pertama, persepsi remaja tentang keberadaan PKPR masih sangat variatif. Kedua, persepsi remaja tentang program PKPR yang diberikan pada remaja, bahwa dari 6 program PKPR belum semua diberikan. Ketiga, harapan remaja terhadap PKPR ke depan bahwa petugas kesehatan harus mampu memberikan penjelasan tentang masalah yang dialami remaja, berlaku seperti sahabat, dan perlu melibatkan remaja, guru BP/UKS, orangtua serta masyarakat dalam pelayanan. Pelayanan dilakukan di tempat remaja berada, yang terjaga kerahasiaannya, waktu pelayanan menyesuaikan jam sekolah, perlu pemanfaatan sms, email untuk komunikasi dan informasi pada remaja.Â Kesimpulan: Remaja memiliki berbagai harapan terhadap PKPR di masa depan. Pelayanan kesehatan yang sesuai dengan harapan remaja dapat dikembangkan sebagai bentuk modifikasi pelayanan kesehatan peduli remaja yang dapat diterapkan di puskesmas.Â Kata Kunci: Pelayanan Kesehatan Peduli Remaja (PKPR), remaja.Â 1Â Â Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Magelang2 Bagian Obstetri Ginekologi, Fakultas Kedokteran Universitas Gadjah Mada Â Â Â Â Yogyakarta3 Program Studi Magister Keperawatan, Universitas Gadjah Mada YogyakartaÂ Â